Implementasi Metode Six Sigma Dengan Pendekatan Taguchi Untuk Menurunkan Tingkat Cacat Pada Proses Produksi Air Conditioner (AC) Indoor di PT Changhong Electric Indonesia - Muhammad Syahrul Amrullah; Mochamad Eko Nugroho; Rakay Edhiargo Toyosito; Sita Kurniaty Ratoko; Lifia Citra Ramadhanti (Science and Education Journal (SICEDU), 2026)
Product quality is one of the primary factors determining the competitiveness ofmanufacturing companies. A high defect rate increases production costs, reduces productivity,and decreases customer satisfaction. PT Changhong Electric Indonesia continues to experiencea defect rate in the Air Conditioner (AC) Indoor production process that exceeds thecompany's quality standard of 2%. This study aims to identify the major causes of productdefects, evaluate process capability using the Six Sigma methodology, and determine theoptimal process parameter combination through the Taguchi approach. This researchemployed a quantitative approach by integrating the Define, Measure, Analyze, Improve, andControl (DMAIC) cycle with the Taguchi method. Research data were collected from production reports covering the period from June 2025 to January 2026, direct observations,interviews, and company documentation. The analytical techniques included Critical toQuality (CTQ), Defects Per Million Opportunities (DPMO), sigma level analysis, Paretodiagram, Fishbone diagram, Analysis of Variance (ANOVA), Orthogonal Array, and Signalto-Noise Ratio (SNR). The results revealed seven major defect categories, with foreignmaterial defects accounting for 26.0%, unfastened components for 20.7%, and missing spareparts for 14.6% of total defects. The average DPMO was 22,758, with a process capability of3.50 sigma, indicating that the manufacturing process remains at the average industrialperformance level. The Taguchi optimization successfully identified the optimal processparameter combination, leading to reduced process variation and improved product quality.The integration of Six Sigma and Taguchi proved effective in reducing product defects andenhancing process stability in